A review of placenta accreta spectrum and its outcomes for perinatal mental health. (February 2023) - Ayalde, Jeremiah; Epee-Bekima, Mathias; Jansen, Brendan
Objectives: Placenta accreta spectrum conditions are rare, life-threatening disorders of placentation encountered in the perinatal period, with lasting impacts on maternal quality of life and psychological wellbeing. Although the obstetric outcomes are well-known, further review is warranted to explore the psychological sequelae that may accompany these conditions. Conclusions: The occurrence of placenta accreta spectrum during pregnancy is a major life stressor that can contribute to the development of psychiatric co-morbidity including posttraumatic stress disorder, depression and anxiety disorders. Early recognition of psychological distress and symptomatic profile is recommended at all stages of perinatal care complicated by this rare spectrum of conditions.